The boy who was raised as a dog : and other stories from a child psychiatrist's notebook : what traumatized children can teach us about loss, love, and healing - Perry, Bruce Duncan, 1955-; Szalavitz, Maia (Basic Books, 2017)
Includes material on "genocide survivors, witnesses to their own parents' murders, children raised in closets and cages, and victims of family violence" ... explains what happens to the brain when a child is exposed to extreme stress, and the author reveals how today's innovative treatments are helping ease children's pain, allowing them to become healthy adults.